2014
DOI: 10.1080/00268976.2014.901661
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of the surface tension of pure tin from atomistic simulations of liquid–vapour systems

Abstract: Monte Carlo simulations of heterogeneous systems of tin at liquid-vapour equilibrium have been performed at several temperatures from 600 to 1500 K, using a modified embedded atom model potential. Surface tension of the corresponding planar interfaces has been evaluated using the test area method. Calculation results are in good agreement with experiments presenting a maximum deviation of 10% from experiments. In addition, the Monte Carlo simulations provide a temperature coefficient (the derivative of the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…The application of a MEAM potential reported by Ravelo [3] for pure Sn revealed a qualitative agreement with the inviscid solution. A good agreement with the experimental surface tension was reported in the literature for the potential [4]. A four times longer void collapse time was observed in the MD simulations at T = 500 K, which can be associated with partial melting and a higher mechanical stability than that assumed in the RP model.…”
Section: Discussionsupporting
confidence: 89%
“…The application of a MEAM potential reported by Ravelo [3] for pure Sn revealed a qualitative agreement with the inviscid solution. A good agreement with the experimental surface tension was reported in the literature for the potential [4]. A four times longer void collapse time was observed in the MD simulations at T = 500 K, which can be associated with partial melting and a higher mechanical stability than that assumed in the RP model.…”
Section: Discussionsupporting
confidence: 89%
“…5,6 To do so, we used potentials based on the Embedded Atoms Model (EAM). 7,8 We have shown that those force fields are well suited to simulate liquid metallic sheets and to produce accurate surface tensions.…”
Section: Introductionmentioning
confidence: 99%